Implementation of the Corporate Criminal Responsibility System as the Subject of Criminal Acts in the Law on the Eradication of Criminal Acts of Corruption - Mashendra Mashendra; Amrun Kahar; LM Karim; Jamil Jamil; Masdiana Masdiana (Budapest International Research and Critics University, 2022)
Accentuation of the development of science and technology today provides changes about subject of follow-up only involved natural people (naturlijke persoon), but at the present, legal entity (rechts persoon) became the subject of judicial actions. Purpose of this research is to determine the corporate criminal liability system as subjects of criminal acts in the Corruption Eradication Act. This research is descriptive research with normative juridical research type, uses statute and conceptual approaches. Data was collected through literature study, then analyzed qualitatively. This research shows that the corporate criminal liability system in Corruption Eradication Act adheres to a mixed corporate criminal liability system, thereby that criminal liability is applied to the corporation and/or its management.